Dipeptidyl peptidase IV, which probably plays important roles in Alzheimer disease (AD) pathology, is upregulated in AD brain neurons and associates with amyloid plaques. (March 2018) - Bernstein, Hans-Gert; Dobrowolny, Henrik; Keilhoff, Gerburg; Steiner, Johann
Abstract: There is evidence from in vitro experiments that dipeptidyl peptidase IV (DPP IV) might play role(s) in amyloid formation. However, nothing is known about the localization of the enzyme in brains of individuals with Alzheimer's disease. We herein show that in comparison to non-demented controls DPP IV is upregulated in AD brain neurons and occurs in multiple amyloid plaques.